Phosphatidylserine liposomes induce a phagosome acidification-dependent and ROS-mediated intracellular killing of Mycobacterium abscessus in human macrophages - Olimpieri, Tommaso; Poerio, Noemi; Ponsecchi, Greta; Di Lallo, Gustavo; D’Andrea, Marco Maria; Fraziano, Maurizio (Frontiers in Cellular and Infection Microbiology, 2024)
Mycobacterium abscessus (Mab) is an opportunistic nontuberculous mycobacterium responsible of difficult-to-treat pulmonary infections in vulnerable patients, such as those suffering from Cystic Fibrosis (CF), where it represents a major cause of morbidity and mortality. Additionally, due to the intrinsic extensive antimicrobial resistance spectrum displayed by this species and the side effects reported for some available antibiotics, the therapeutic management of such infections remains extremely difficult. In the present study, we show that phosphatidylserine liposomes (PS-L) enhance intracellular mycobacterial killing of Mab infected human macrophages with functional or pharmacologically inhibited cystic fibrosis conductance regulator (CFTR), by a mechanism involving phagosome acidification and reactive oxygen species (ROS) production. Additionally, PS-L significantly reduce proinflammatory response of Mab infected macrophages in terms of NF-kB activation and TNF-α production, irrespective of CFTR inhibition. Altogether, these results represent the proof of concept for a possible future development of PS-L as a therapeutic strategy against difficult-to-treat Mab infection.